Higantes int(er)act converging digital media process, forms and experiences with the culture, heritage and arts of Angono, Rizal - Manuel, Gerimara Vinaya S.; Villajuan, Jose Dan V. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The Municipality of Angono in Rizal, recognized as the "Art Capital of the Philippines", is in need of new tourist destinations and new tourism products and services because the level of gaining the sought out "art experience" is reaching its limitations as stated on their 2006-2010 Medium-Term Art Tourism Development Plan. Concurrently, the local government is also beginning to implement various projects and programs related with traditional animation, graphic design services and information technology among its locality. Given this crisis and this advent of developments, the study proposes landscape approach and strategies that merges digital media processes, forms and experiences and integrates it with the culture, heritage and arts of the municipality through landscape planning and design. In this paper, the suitability of conceptual spatial zones and facilities that maximizes the application of digital media based on municipality tourism development plan was examined. The research presents different digital media technologies that will accommodate current critical art practices in the community and discusses to what extent could these characteristics of digital media can correspond to the needs of several local artists, cultural organizations and art developers.
includes appendices.
Best Thesis (Landscape Architecture) AY 2016-2017, 2nd place
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman